Load flow studies of electrical power system using Newton-Raphson method / Zulhairi Abdul Razak - Abdul Razak, Zulhairi (1999)
Various method of load flow solution in electrical power system has been developed to find better load flow solution. In this thesis, Newton-Raphson method of load flow solution was used as a model for the purpose of this project. Combining it with C++ programming language, the program developed gives a description on how it is computed and further developed as a software. To view how the process is working an electrical power system model of IEEE 9 and 14-bus interconnected system were simulated using above method. The software developed in this project is capable of executing as high as 25 bus of interconnected system. A graphic user interface (GUI) was created using Borland C++ tools to allow easy manipulation of input data and easy viewing of output results. The program is later developed as an execution program to demonstrate how it is operated as actual operating software.